Shortening the Diagnostic Odyssey: The Role of AI in Genomic Analysis for Rare Disease Diagnosis - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The diagnosis of a rare disease RD often marks the beginning of a long and arduous journey for patients and their families, a period widely known as the "Dia...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine; Machine Learning